2022
DOI: 10.3389/fsurg.2022.1022937
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of direct anterior approach vs. other surgical approaches for total hip arthroplasty: A systematic review and meta-analysis based on RCTs

Abstract: BackgroundDirect anterior approach (DAA) is an accurate technique for total hip arthroplasty (THA) through the muscle gap. Physicians who apply DAA believe that it accelerates patient recovery and results in lower rates of postoperative dislocation. However, the traditional surgical approach adherents believe that it is shorter and has fewer complications than DAA.MethodsWe use the method of META analysis to organize and analyze the data of the randomized controlled studies (RCT) obtained after our screening. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…For the first part, 28 MAs[ 6 , 20 - 46 ] were identified from PubMed and Scopus according to PICOS, including 61 RCTs. Finally, 40 RCTs were retrieved from previous MAs after screening for the eligible criteria and removing duplicated studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first part, 28 MAs[ 6 , 20 - 46 ] were identified from PubMed and Scopus according to PICOS, including 61 RCTs. Finally, 40 RCTs were retrieved from previous MAs after screening for the eligible criteria and removing duplicated studies.…”
Section: Resultsmentioning
confidence: 99%
“…Many systematic reviews and meta-analysis (MA) of THA[ 6 , 20 - 46 ] showed that DAA could be beneficial for early hip function, and post-operative pain than other techniques[ 6 , 23 , 28 , 30 , 34 - 36 , 42 , 44 , 45 ]. Contradictory, it came up with a higher incidence of nerve injury[ 28 , 32 , 42 , 45 , 47 ], and inconsistent issues of other complications[ 6 , 31 , 37 , 39 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed a slightly lower dislocation rate in the group of patients operated via DAA. However, studies with larger numbers of patients could no longer detect a significant difference [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no functional difference between the 2 groups were noticed when looking at 6-month Harris hip scores [ 35 ]. While the literature indicates different surgical approaches have variable muscle damage, most studies reveal equal outcomes around 6 weeks postoperatively and further research is warranted in this field [ 36 ].…”
Section: Approaches In Total Hip Arthroplastymentioning
confidence: 99%